Neuroimmune communication in allergic rhinitis - Zhou, Yi; Chen, Ru; Kong, Lili; Sun, Yaoyao; Deng, Jing (Frontiers in Neurology, 2023)
The prevalence rate of allergic rhinitis (AR) is high worldwide. The inhalation of allergens induces AR, which is an immunoglobulin E-mediated and type 2 inflammation-driven disease. Recently, the role of neuroimmune communication in AR pathogenesis has piqued the interest of the scientific community. Various neuropeptides, such as substance P (SP), vasoactive intestinal peptide (VIP), calcitonin gene-related peptide (CGRP), nerve growth factor (NGF), and neuromedin U (NMU), released via “axon reflexes” or “central sensitization” exert regulatory effects on immune cells to elicit “neurogenic inflammation,” which contributes to nasal hyperresponsiveness (NHR) in AR. Additionally, neuropeptides can be produced in immune cells. The frequent colocalization of immune and neuronal cells at certain anatomical regions promotes the establishment of neuroimmune cell units, such as nerve-mast cells, nerve-type 2 innate lymphoid cells (ILC2s), nerve-eosinophils and nerve-basophils units. Receptors expressed both on immune cells and neurons, such as TRPV1, TRPA1, and Mas-related G protein-coupled receptor X2 (MRGPRX2) mediate AR pathogenesis. This review focused on elucidating the mechanisms underlying neuroimmune communication in AR.